Classification of motor imagery electroencephalogram signals by using adaptive cross-subject transfer learning - Feng, Jin; Li, Yunde; Jiang, Chengliang; Liu, Yu; Li, Mingxin; Hu, Qinghui (Frontiers in Human Neuroscience, 2022)
Electroencephalogram (EEG) based motor imagery (MI) classification is an important aspect in brain-computer interfaces (BCIs), which bridges between neural system and computer devices decoding brain signals into recognizable machine commands. However, due to the small number of training samples of MI electroencephalogram (MI-EEG) for a single subject and the great individual differences of MI-EEG among different subject, the generalization and accuracy of the model on the specific MI task may be poor. To solve these problems, an adaptive cross-subject transfer learning algorithm is proposed, which is based on kernel mean matching (KMM) and transfer learning adaptive boosting (TrAdaBoost) method. Firstly, the common spatial pattern (CSP) is used to extract the spatial features. Then, in order to make the feature distribution more similar among different subjects, the KMM algorithm is used to compute a sample weight matrix for aligning the mean between source and target domains and reducing distribution differences among different subjects. Finally, the sample weight matrix from KMM is used as the initialization weight of TrAdaBoost, and then TrAdaBoost is used to adaptively selects source domain samples that are closer to the target task distribution to assist in building a classification model. In order to verify the effectiveness and feasibility of the proposed method, the algorithm is applied to BCI Competition IV datasets and in-house datasets. The results show that the average classification accuracy of the proposed method on the public datasets is 89.1%, and the average classification accuracy on the in-house datasets is 80.4%. Compared with the existing methods, the proposed method effectively improves the classification accuracy of MI-EEG signals.